Polymorphism of the Fractalkine Receptor CX3CR1 and Systemic Sclerosis-associated Pulmonary Arterial Hypertension - Bianca Marasini; Roberta Cossutta; Carlo Selmi; Maria Rosa Pozzi; Marco Gardinali; Marco Massarotti; Maddalena Erario; Lodovica Battaglioli; Maria Luisa Biondi (Clinical and Developmental Immunology)
Fractalkine (FKN) and its receptor CX3CR1 are critical mediators in the vascular and tissue damage of several chronic diseases, including systemic sclerosis (SSc) and pulmonary arterial hypertension (PAH). Interestingly, the V249I and T280M genetic polymorphisms influence CX3CR1 expression and function. We investigated whether these polymorphisms are associated with PAH secondary to SSc. CX3CR1 genotypes were analyzed by PCR and sequencing in 76 patients with limited SSc and 204 healthy controls. PAH was defined by colorDoppler echocardiography. Homozygosity for 249II as well as the combined presence of 249II and 280MM were significantly more frequent in patients with SSc compared to controls (17 vs 6%, p = 0.0034 and 5 vs 1%, p = 0.0027, respectively). The 249I and 280M alleles were associated with PAH (odd ratio [OR] 2.2, 95% confidence interval [CI] 1.01-4.75, p = 0.028 and OR 7.37, 95%CI: 2.45-24.60, p = 0.0001, respectively). In conclusion, the increased frequencies of 249I and 280M CX3CR1 alleles in a subgroup of patients with SSc-associated PAH suggest a role for the fractalkine system in the pathogenesis of this condition. Further, the 249I allele might be associated with susceptibility to SSc.